2015
DOI: 10.1111/rda.12600
|View full text |Cite
|
Sign up to set email alerts
|

Stress Response of Veterinary Students to Gynaecological Examination of Horse Mares – Effects of Simulator‐Based and Animal‐Based Training

Abstract: Invasive procedures in animals are challenging for veterinary students who may perceive a gynaecological examination of mares as stressful. Simulator-based training may reduce stress. In this study, students received equine gynaecology training 4 times either on horses (group H; n = 14) or a teaching simulator (group SIM; n = 13). One day and 14 days thereafter, their diagnostic skills were tested on horses (skills tests 1 and 2). During the skills tests, the students' stress response was analysed by heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In the situation 3, the questionnaire indicated a low degree of stress in students and therefore did not agree with sAA values. This lack of agreement between questionnaires and salivary stress biomarkers such as cortisol, has also been identified in previous reports about veterinary students responses to different activities, for example public oral speech [16], gynaecological examination of horses [30], and in others psychological studies [31]. In addition, Campbell and Ehlert [31] have identified various elements that potentially contribute to the apparent dissociation between the emotional and the physiological response in acute psychosocial stress models such as underlying psychological traits and states.…”
Section: Discussionmentioning
confidence: 58%
“…In the situation 3, the questionnaire indicated a low degree of stress in students and therefore did not agree with sAA values. This lack of agreement between questionnaires and salivary stress biomarkers such as cortisol, has also been identified in previous reports about veterinary students responses to different activities, for example public oral speech [16], gynaecological examination of horses [30], and in others psychological studies [31]. In addition, Campbell and Ehlert [31] have identified various elements that potentially contribute to the apparent dissociation between the emotional and the physiological response in acute psychosocial stress models such as underlying psychological traits and states.…”
Section: Discussionmentioning
confidence: 58%
“…Nine of the 73 articles reviewed (12.3%) focused on equine simulators. All of the studies were experimental, and the techniques included: intravenous and intramuscular injections; 29 intra-articular (joint) injections; 30 diagnostic regional anaesthesia (nerve blocks); 31 endoscopy of the upper respiratory tract; 32 gynaecological examination; 33,34 laparoscopic ovariectomy; 35 and cardiac dissection. 36 Cardiac dissection was included as a clinical skill for the purposes of this article, due to the RCVS listing the ability to perform a post-mortem examination in their Day One Competences, and the assumption that the cardiac dissection procedure would be required as part of a thorough post-mortem examination.…”
Section: Resultsmentioning
confidence: 99%
“…43 Table 1 provides a summary of all the simulators described in the reviewed literature. 14,15,19,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]…”
Section: Simulators Applicable To All Speciesmentioning
confidence: 99%
“…It is essential to train students in these reproductive techniques and offer the opportunity to perform the technique in inert models to reduce the stress of both animal and operator. In 2015, Nagel et al [28] found that the cortisol levels and heart rate of students performing ultrasound examination in a simulator were lower than those who performed it directly on living animals. Simulators as educational tools can help students to overcome their anxiety while practicing some procedures [29], improving their learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Nagel et al . [ 28 ] found that the cortisol levels and heart rate of students performing ultrasound examination in a simulator were lower than those who performed it directly on living animals. Simulators as educational tools can help students to overcome their anxiety while practicing some procedures [ 29 ], improving their learning curve.…”
Section: Discussionmentioning
confidence: 99%